Upstream and Downstream Wind‐Stress Forcing of Seasonal Variability of Luzon Strait Deep Overflow Transport - Lei Chen; Jiayan Yang; Lixin Wu (Geophysical Research Letters)
Abstract The Luzon Strait Deep Overflow (LZDO) transports deep‐water masses from the Pacific Ocean (upstream) to the South China Sea (SCS, downstream), playing a vital role in shaping the hydrographic and biogeochemical structure and regulating abyssal circulation within the SCS. Recent studies suggest that the seasonal variability of LZDO transport is primarily wind‐driven; however, the specific mechanisms and key wind‐forcing areas remain unclear. In this study, we use numerical model experiments to demonstrate that the seasonal variability of the LZDO is driven by wind stress both within the downstream SCS and upstream Pacific Ocean. This finding contrasts with previous views that considered the LZDO hydraulically controlled at the Luzon Strait sill and thus influenced solely by the upstream Pacific Ocean forcing. Additionally, we identify that the LZDO is particularly sensitive to wind forcing in specific North Pacific regions where geostrophic contours connect to the Luzon Strait due to topographic effects.